Confirmatory Factor Analysis of Effective Fitness Centers in Bangkok Metropolitan Region - Chankuna, Dittachai (Academic Journal of Thailand National Sports University, 2018)
The major objective of this research was to analyze effective fitness center managerial factors in Bangkok metropolitan region based on Competing Value Approach (CVA) theory. Samples were 660 members in 37 branches of effective fitness centers. Instrument was questionnaire developed from Chankuna (2013) and Shilbury & Moore (2006). Statistics used was confirmatory factor analysis with fix factor method by Mplus software. The results were found that a factor model of effective fitness center in Bangkok metropolitan region was moderate fit (CFI = 0.860). Standardized factor loading of 8 factors were Marketing Strategy (0.972) Consumer Behavior (0.897) Human Resource Management (0.895) Consumer Relation (0.881) Service and Product (0.871) Organization Development (0.847) Career Path (0.837) and Planning and Organizing (0.820). Standard of trainer was high importance for effective fitness centers management